Functional characterization of lon channels with a crucial role in cystic fibrosis : regulation of epithelial Na+chanel (ENaC) and Ca2+-activated Cl- channels (CaCCs) in epithelial cells - Almaça, Joana Collares Pereira, 1984- (2011)
Tese de doutoramento, Bioquímica (Genética Molecular), Universidade de Lisboa, Faculdade de Ciências, 2011